Development, Characterization, Sintering, Dielectric and Optical Properties of NdBa2ZrO5·5 Nanocrystals - Rajan, Jose; Kumar, V. Ratheesh; Wariar, P. R. S.; Pazhani, R.; Thomas, J. K.; Koshy, J. (Springer-Verlag, 2012)
Nanocrystalline NdBa2ZrO5 ·5 has been successfully synthesized through a single step auto-ignition combustion route for the first time. X-ray diffraction and Fourier transform infrared spectroscopy revealed that the combustion product is phase pure and has an ordered cubic perovskite structure. The phase transitions and thermal stability of the nanopowder were investigated by differential thermal and thermogravimetric analyses. Transmission electron microscopy results indicated that the particle sizes are 20–30 nm. Selected area electron diffraction pattern has shown that as-prepared powder is polycrystalline in nature. The optical absorption spectra analysis confirmed that the material falls to the semiconducting range with a bandgap of ~3 ·69 eV and therefore, could be used as transparent wide bandgap semiconductor. The relative density of the sintered sample is ~96% at 1510 °C for 2 h. The surface morphology of the sintered pellet has been studied by scanning electron microscopy and the average grain size observed is ~0·7 μm. Dielectric constant (ε r) of NdBa2ZrO5·5 at 5 MHz is 29·6 and loss factor (tan δ) is 4 ×10 − 2 at room temperature.